INNV-10. EFFECTS OF TTFIELDS USAGE AND DURATION OF USAGE ON CELLULARITY AND Ki67 DISTRIBUTIONS AT AUTOPSY. (9th November 2020) - Bobholz, Samuel; Lowman, Allison; Connelly, Jennifer; Cochran, Elizabeth; Mueller, Wade; McGarry, Sean; Brehler, Michael; LaViolette, Peter
Abstract: This study used autopsy tissue samples taken from patients with glioblastoma who had undergone Tumor-Treating Fields (TTFields) therapy to examine the effects of treatment usage and duration on cellular and mitotic activity distributions. We hypothesized that treatment duration and percent compliance would be associated with a change in cellularity. Three tissue samples were collected from 10 patients with glioblastoma at autopsy. These samples were specifically collected in regions that demonstrated clear contrast enhancement on the patients' last clinical imaging, in order to capture regions of suspected active tumor. Samples were stained with both hematoxylin and eosin (HE) and Ki67 immuno-histochemistry (IHC) and digitized at 40X resolution using a digital microscope. A color deconvolution algorithm was used to separate stains, which allowed nuclei segmentation. Number of cells and percent of Ki67 positive cells were computed across 100x100 superpixels. Spearman's correlations were used to examine the association between TTFields usage (measured as a percent) and duration of use (in days) and signatures of active tumor proliferation, measured as median cellularity and proportion of Ki67 positive cells across each patients' three samples. Trending negative associations with median cellularity were observed for both TTFields usage (R=-0.60, p=0.065) and duration (R=-0.61, p=0.063). The magnitude of the treatment duration effect increased when controlling for time between diagnosis and death, despite a p-value drop due to the lost statistical degree of freedom (R=-0.62, p=0.073). No significant effects were observed for Ki67 positive staining. These results generally suggest a possible effect of TTFields therapy duration, where longer treatments and increased compliance lead to lower tumor proliferation. However, these results should be interpreted with caution, as larger, more statistically powerful studies will be better suited to assess the generalizability of the preliminary trends seen in these RESULTS: